Gambaran Kadar Glukosa Darah Menggunakan Sampel Serum dan Plasma EDTA - Anita, Anita; Fatmawati, Andi; Arisanti, Dewi; Jasman, Hendra; Nurmaulidya (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Blood glucose is a sugar in the blood that is formed from carbohydrates and then stored in the form of glycogen in the liver and skeletal muscles. Chemically, glucose content examination using EDTA plasma is rarely used. The difference between plasma and serum occurs because serum does not form fibrinogen and some other coagulation factors, whereas plasma still has all the proteins and anticoagulant particles that can affect the examination. This study aims to determine the picture of blood glucose levels using serum and EDTA plasma samples. This study was conducted through laboratory observation which aims to determine the picture of blood glucose levels using serum and EDTA plasma samples. The number of samples used was 10 blood which was then separated between serum and plasma samples. The objects in this study were serum and EDTA plasma using the GOD PAP method. The results of this study were that the average level of blood glucose examination when using serum samples was 89.7 mg / dL, while using EDTA plasma samples 103 mg / dL. So it can be concluded that the average blood glucose level in EDTA plasma is higher than serum